VEGF expression in colorectal cancer metastatic lymph nodes: clinicopathological correlation and prognostic significance - Mazeda, Inês (2020)
Background: Angiogenesis plays an important role in colorectal cancer (CRC) tumorigenesis and metastatic progression. Methods: The present series consisted of CRC lymph node metastasis (LNM) tissue samples from 210 patients. Archival paraffin embedded LNM tissue were used to build up tissue microarray blocks and VEGF expression was immunohistochemically assessed. Results: VEGF-A and VEGF-C are overexpressed in LNM. VEGF-A was associated with patient age (p < 0.001), and VEGFR-2 and VEGFR-3 with CRC relapse (p = 0.032; p = 0.030, respectively). VEGF-C positivity was associated with VEGFR-3 positivity (p = 0.031), and VEGF-D with VEGFR-2 and VEGFR-3 (p ≤ 0.001). Matching the expression in LNM with CRC, in CRC VEGF-A positivity associates with VEGF-A, VEGF-C, VEGF-D, VEGF-R2, VEGF-R3 positivity in LNM; CRC VEGF-C with VEGF-D, VEGFR-2, VEGFR-3; CRC VEGFR-2 with VEGF-A, VEGF-C, VEGF-D, VEGFR-2, VEGFR-3; CRC VEGFR-3 with VEGF-A, VEGF-C, VEGF-D, VEGFR-2, VEGFR-3 in LNM. Conclusion: This study provides new information, revealing that VEGF family expression is increased in LNM. The association between the expression of VEGFR-2 and VEGFR-3 in LNM with CRC relapse reveals its impact on patient prognosis. Interesting data were found when the relationship between these proteins in primary tumor and their metastasis, were analyzed; VEGFA positivity in primary tumor is positively related to VEGF-A, VEGF-C, VEGF-D, VEGFR-2 and VEGFR-3 in their respective LNM suggesting mutual influence.